Pengaruh Intellectual Capital, Pembiayaan Jual Beli, Pembiayaan Bagi Hasil, Pembiayaan Ijarah, Dan NonPerforming Financing Terhadap Profitabilitas Dengan Biaya Operasional Dan Pendapatan Operasional Sebagai Variabel Intervening Pada Bank Umum Syariah Di I - Fitri Yani; Widya Astuti; Maya Sari (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
This study aims to analyze the effect of intellectual capital, buying and selling financing, profit sharing financing, ijarah financing, and non-performing financing on the profitability of Islamic Commercial Banks with Operating Costs and Operating Income as intervening variables. This type of research is a case study with a quantitative approach with data collection techniques through documentation studies using secondary data. The research population is Islamic Commercial Banks in Indonesia registered with the Financial Services Authority. The data collection technique is by purposive sampling. The samples taken were 13 Islamic Commercial Banks. The observation year starts from 2016-2020. The data analysis technique in this study used a Structural Equation Modeling (SEM) type of SEM Partial Least Squares (SEM-PLS). The SEM-PLS software used is Smart-PLS 3.2.9. The results of this study indicate that intellectual capital, buying and selling financing, profit sharing financing, and ijarah financing each have no effect on the return on assets (ROA) of Islamic commercial banks. NPF affects the return on assets (ROA) of Islamic commercial banks. BOPO affects the return on assets (ROA) of Islamic commercial banks. Intellectual Capital and NPF each have no effect on BOPO. Sale and Purchase Financing, Profit Sharing Financing, and Ijarah Financing each have an effect on BOPO. Intellectual Capital has no effect on return on assets (ROA) of Islamic commercial banks through BOPO. Intellectual Capital has no effect on return on assets (ROA) of Islamic commercial banks through BOPO. Sale and purchase financing has a significant effect on the return on assets (ROA) of Islamic commercial banks through BOPO. Profit sharing financing has a significant effect on the return on assets (ROA) of Islamic commercial banks through BOPO. Ijarah financing has a significant effect on the return on assets (ROA) of Islamic commercial banks through BOPO. NPF has no effect on return on assets (ROA) of Islamic commercial banks through BOP.